Field-Theoretic Simulations of Binary Blends of Complementary Diblock Copolymers - Willis, James (University of Waterloo, 2026)
The phase behavior of binary blends of AB diblock copolymers of compositions f and 1 − f is examined using field-theoretic simulations. Highly asymmetric compositions (i.e., f ≈ 0) behave like homopolymer blends macrophase separating into coexisting A- and B- rich phases as the segregation is increased, whereas more symmetric diblocks (i.e., f ≈ 0.5) microphase separate into an ordered lamellar phase. In self-consistent field theory, these behaviors are separated by a Lifshitz critical point at f = 0.2113. However, its lower critical dimension is believed to be four, which implies that the Lifshitz point should be destroyed by fluctuations. Consistent with this, it is found to transform into a tricritical point. Furthermore, the highly swollen lamellar phase near the mean-field Lifshitz point disorders into a bicontinuous microemulsion (BμE), consisting of large, interpenetrating A- and B-rich microdomains. A BμE has been previously reported in ternary blends of AB diblock copolymers with its parent A- and B-type homopolymers, but in that system the homopolymers have a tendency to macrophase separate. Our alternative system for creating BμE is free of this macrophase separation.
Keywords: polymer; NATURAL SCIENCES::Physics::Other physics::Statistical physics; NATURAL SCIENCES::Chemistry::Theoretical chemistry::Statistical mechanics; NATURAL SCIENCES::Physics::Condensed matter physics::Critical phenomena (phase transitions)